Statistical analysis of early marriage among women in Ethiopia by using multilevel logistic regression - Tezera Abebe Gashaw (Global Journal of Fertility and Research - Peertechz Publications, 2019)
Early marriage is still widely practiced in many parts of the world mainly in Latin America, the Caribbean, Southern Asia and countries of Africa. Ethiopia has one of the highest rates of early marriage in Sub-Saharan Africa. The main objective of this study was to identify determinants of early marriage among women in Ethiopians and to examine variations in early marriage between and within regions of Ethiopia. The study is made based on the Ethiopian Demographic and Health Survey 2011 data that has two stages sampling hierarchical structure, collected for 9262 married women nested within eleven regions with age 15-49 years. Descriptive statistics and multilevel logistic regression model analysis were used to examine the prevalence and identify determinants of early marriage. The results of descriptive statistics shows that Out of the 9,262 married women, 3320(35.8%) of marriages occur 18 years and above while 5942 (64.2%) of these women married early (under 18 years) at the time of the survey.